2018
DOI: 10.1080/07853890.2018.1443346
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of bullous pemphigoid: an update on this stubborn clinical problem

Abstract: Bullous pemphigoid (BP) is a chronic autoimmune blistering disorder that has a predilection for the elderly. It is characterized by a poor prognosis due to its high mortality rate and the tendency to relapse. The relapse rate of BP ranges from 27.87% to 53% after disease remission, while the majority of relapses occur early (within 6 months) during remission. Clinical interventions aimed to prevent early relapses could reduce potential complications from first-line treatment and make follow-up care easier for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…Our analysis of the correlation between IL-13 and recurrence found that both the rs20541 and rs1800925 genotypes significantly correlate with recurrence, suggesting that patients with some genotypes be genetically more susceptible. Relapse in BP remained a persistent issue for patients and clinicians and has contributed substantially to the morbidity and mortality from BP ( 36 ). Because high IL-13 expression and gene polymorphisms are associated with BP and clinical relapse of BP, we hypothesize that IL-13 gene polymorphisms have an effect on IL-13 gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis of the correlation between IL-13 and recurrence found that both the rs20541 and rs1800925 genotypes significantly correlate with recurrence, suggesting that patients with some genotypes be genetically more susceptible. Relapse in BP remained a persistent issue for patients and clinicians and has contributed substantially to the morbidity and mortality from BP ( 36 ). Because high IL-13 expression and gene polymorphisms are associated with BP and clinical relapse of BP, we hypothesize that IL-13 gene polymorphisms have an effect on IL-13 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…BP patients were followed up by telephone calls or in our outpatient office for prognostic information. The definition of relapse is the appearance of at least three new lesions in one month (including blisters, urticarial plaques, or eczematous lesions) or no less than one large (>10 cm in diameter) urticarial plaque or eczematous lesion that does not heal within one week, or the extension of original lesions or daily pruritus in the adequately managed patients within disease control ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…One finding revealed a significant association between dermal eosinophilia and severity of BP ( 46 ). An elevated eosinophil count is thought to increase the risk of relapse and is a predictor of poor prognosis ( 47 ). Thus, eosinophils may be a putative therapeutic target for BP.…”
Section: Risk Factorsmentioning
confidence: 99%
“…El penfigoide ampolloso (PA) se caracteriza por episodios espontáneos de exacerbaciones y remisiones (meses o años); 30% de los pacientes recae dentro del primer año (aquellos con afección extensa y factores de riesgo como demencia), y 50% reincidirá a los tres meses posterior a la suspensión del tratamiento. 14 El pronóstico se ve afectado por la edad y el estado funcional. La mortalidad en adultos mayores de países occidentales durante el primer año se calcula en 10-40%.…”
Section: Pronósticounclassified